Kradetzut na praskovi - Radev, Valo (Bulgaria : Studio for Feature Films, 1964)
The end of WWI draws near. The commandant of the town of Veliko Turnovo, a pedantic officer, keeps his wife Lisa behind the thick walls of his house and a peach tree orchard. One day Lisa’s solitude is broken. She finds Serb prisoner of war Ivo Obrenovich in her garden . Hunger has driven him out of the POW camp. The compassion awoken in the young woman soon turns into passionate love. They realize soon that in the chaos of agony and madness their love is doomed, but this makes it even greater. The husband becomes aware of the change in Lisa. In the town riots start and he orders the camp to be relocated. Ivo runs out of the column of POWs to say goodbye to Lisa and is shot by a guard.
Duration: 01:43:00
Keywords: Fiction films